Decrased sputum caveolin-1 is associated with systemic sclerosis related lung disease - Yilmaz, Neslihan; Olgun, Sehnaz; Ahiskali, Rengin; Karakurt, Sait; Yavuz, Sule (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
AIM: To determine serum and sputum Caveolin-1 (Cav-1) levels and their associations with transforming growth factor- ß (TGF-ß) and interstitial lung disease (ILD) in systemic sclerosis (SSc).METHODS: Serum and induced sputum samples from 55 patients with SSc, 25 asthma patients and 16 healthy volunteers (HC) were tested for Cav-1 and TGF-ß by the ELISA technique. As a possible downstream signaling regulator of TGF-ß, Endothelin-1 (ET-1), a potent profibrotic protein, was also measured in all serum and sputum samples and relations with Cav-1 and TGF-ß were sought.  All scleroderma patients were evaluated for their clinical and laboratory parameters. Pulmonary function tests (PFT) and high resolution computerized tomography (HRCT) were performed for the diagnosis of ILD. The alveolitis-fibrosis index and the SSc disease severity scores were noted for each patient.RESULTS:  Serum Cav-1 levels were lower in SSc compared to HC (p